Approach to the Core Structure of 15-epi-Exiguolide - Riefert, Alexander; Maier, Martin E. (Synthesis, 2018)
The synthesis of seco acid 41 of the macrolactone part of 15-epi-exiguolide, containing a bis-pyran subunit and a trans double bond, is described. Key features of the synthetic strategy include a Feringa–Minnaard asymmetric organocuprate addition to unsaturated ester 17 to set the stereocenter at C15. The derived acid 8 (C9–C16 fragment) was ideally suited for combination with aldehyde 9 (C17–C21 fragment) via an aldol strategy leading to β-lactone 25 which upon thermal decarboxylation provided alkene 26. Chain extension led to propargylic alcohol 7. Treatment of 7 with a LAu+ catalyst promoted a Meyer–Schuster rearrangement to enone 30 that led to cis-tetrahydropyran 31 via intramolecular oxa-Michael reaction. The second pyran ring was prepared from alkoxy ketone 5 by reductive cyclization. The further steps toward macrolactone 43 were hampered by the epimeric mixture at C5.
Keywords: exiguolide; β-lactone; Meyer–Schuster rearrangement; tetrahydropyrans; alkenes; Mulzer–Adam olefination